The Social Role of Islamic Banks in Indonesia during the Pandemic of COVID-19: Reflection of Market Share - Abbas, Ahmad; Frihatni, Andi Ayu (European Journal of Islamic Finance, 2020)
The objective of this research is to reveal the social role of Islamic banks in Indonesia in helping the nation survive in the midst of COVID-19 pandemic in the context of market share. This research highlights Islamic commercial banks in Indonesia. The mixed research method under sequential explanatory model is used in this research. The result of this research demonstrates that banks with the largest magnitude have shown a fixed position. There is no change of position on their concentration ratio at pre and along pandemic period. The final result of this research finds that all the banks have implemented their social role in the midst of coronavirus outbreak through the donation. A self-protection assistance tool for health workers is the type of donation provided by all the banks. Further finding in this research reveals that the magnitude of market share owned by the banks tends to reflect types of social involvement.